Editor's Note - Terdudomtham, Thamavit (Journal of Contemporary Social Sciences and Humanities, 2025)
As of May 1, 2021, the number of COVID-19 infection cases has risen to more than 153 million globally, and 3.2 million related deaths have been reported (WHO). In the midst of this crisis, there is hope for an end of the pandemic by COVID-19 vaccines and public health measures. However, unequal vaccine distribution may be an unexpected obstacle. According to United Nations (April 16, 2021), of the 832 million vaccine doses distributed worldwide, 82 percent have gone to high- or upper-middle-income countries, while only 0.2 percent have gone to low-income countries. However, WHO and UNICEF have urged all relevant departments to work together to ensure fair and equitable access to the COVID-19 vaccine, which is critical for the end of this pandemic. Under this complicated situation, our society needs to learn new knowledge and ideas for ending the pandemic and having sustainable development, with the principle of “leaving no one behind.” Our journal intends to act as a medium for presenting the said knowledge and ideas to our society.